The Problem of Rationalization of Uses of Force in the Conduct of Foreign Policy by a State - Stanislav Valentinovich Korostelev (Управленческое консультирование)
This article explores the problem addressing the process of international rationalization of uses of force in the conduct of foreign policy by states. Behavior of states is to a great extent preconditioned by the existence of an obligation to interpret the rules of international law publicly. Author defines the subject matter of the process of international rationalization of uses of force and the basic missions of it. Additionally the article does evolve the coherence of that process with military doctrine and translated into reality national security strategy.